Pengembangan Motorik Kasar melalui Kegiatan Senam Kreasi pada Anak PAUD Balai Pengajian Baitul Ishlah Lhokseumawe - Elfiadi, Elfiadi; Munasti, Desiva (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2022)
This study aims to develop children's gross motor skills through creative gymnastics activities at the Baitul Ishlah Lhokseumawe Study Center. The type of research used is classroom action research. The technique of collecting data using interviews, observation, and documentation with qualitative descriptive data analysis techniques. The results showed that creative gymnastics activities can develop gross motor skills of the children in the Baitul shlah Lhokseumawe Research Center. Cycle I show the gross motor development of children who have not developed as many as 4 children or 11 children who are developin and those who are developing according to expectations and developing very well do not exist. In the second cycle, there was gross motoric development of the children, namely 13 very well-developed children and 2 children who developed according to expectations, while there were no more children who began to develop and had not developed. As for how to develop children's gross motor skills through creative gymnastics activities carried out by the steps 1) Stand up straight while stretching out your arms as in a prayer movement, opening your legs and looking forward. 2) do the walking in place, stretch your hands to the left and right then swing your hands forward while shaking them. 3) Walk sideways to the left and right while shaking hands, cutting right and left movements while stomping alternately. 4) The legs are shoulder-width apart, arms straight up and do up and down movements forwards and backwards and leaning the left and right sides.